Perfil de utilização do análogo glargina da insulina para o tratamento do Diabetes Mellitus Tipo I no Estado de Minas Gerais, Brasil - Ana Luisa Caires de Souza (2012)
Introduction: Diabetes mellitus is a disease of great social and economic impact with relevant indicators in health. To control it requires a complex interaction of several factors, such as treatment adherence, diet, physical activity and body weight control. The insulin analogueswere developed to increase the convenience and safety of the diabetes treatment. Glargine was the first analogue marketed and due to growing lawsuit it was embodied the relationship of drugs in Minas Gerais for the treatment of diabetes mellitus type 1. There are about 2700 people receiving the drug and spending treasure totaled approximately $ 10 million in 2011. Moreover, recent studies do not support the superiority of this analogue relative to standard insulin. Objective: To analyze the efficacy and the use of glargine for the treatment of T1DM in the State of Minas Gerais, in order to support the public health manager in decisionmaking. Methods: It was performed a Systematic Review of Randomized Clinical Trials focusing on the efficacy of the glargine analogue used for the treatment of type 1 diabetic patients. The search was realized in the databases MEDLINE (PubMed), Latin American andCaribbean Health Sciences (LILACS ), Cochrane Controlled Trials Databases and NHS Centre for Reviews and Dissemination, to identify relevant studies published from January 1970 to July 2009. For a description of the usage profile of glargine was built a historicalcohort of patients assigned to the Regional Health of Belo Horizonte diagnosed with T1D, who received the drug during the period from June 2009 to January 2011. Data were collected from administrative proceedings that reached the State Department of Health / MG foranalysis of the medical referee. The variables socio-demographic, clinical, laboratory, and drug-related were selected for analysis. The variable glycemic control was built, considering the appropriate control value of glycated hemoglobin 7.0% for patients from 20 years, 7.5% for patients between 13 and 19 years and 8% for patients under 12 years. The descriptive statistics of the data was performed by measures of central tendency and dispersion for continuous variables and frequency distributions for categorical variables. It was used the nonparametric Mann-Whitney test for comparison of medians and chi-square test or Fisher's exact test to compare categorical variables. For all statistical analysis was adopted significance level of 5%.Conclusion: The study achieved its primary objective ofevaluating the efficacy and the use of glargine in Minas Gerais. The results found no more effective or fully proven convenience and effectiveness in the use of glargine. It is suggested to the public health manager to disinvest or renegotiation of the prices with the manufacturer.In search of better evidence additional studies must be realized including about selfmanagement of diabetes programs.